Hubungan Nuliparitas Terhadap Kejadian Preeklampsia dengan Penyulit di Rumah Sakit Rujukan Tersier - Jojor Sihotang; Darma Lutfi Ananda; Renardy Reza Razali; Sri Wahyuni (Jurnal Ilmu Kedokteran, 2026)
Maternal Mortality Rate (MMR) remains high globally, particularly in developing countries. In Indonesia, hypertensive disorders of pregnancy, including preeclampsia, are major contributors to maternal mortality. The prevalence of preeclampsia at Arifin Achmad Regional General Hospital was 28.12%. Nulliparity is a known risk factor for preeclampsia; however, no studies have examined its association with complicated preeclampsia in Riau Province. This study aimed to analyze the relationship between nulliparity and the occurrence of complicated preeclampsia. This observational analytic study employed a retrospective cross-sectional design using secondary data from medical records of preeclampsia patients at Arifin Achmad Regional General Hospital, Riau Province, from 2019 to 2022. Consecutive sampling was applied to include all patients meeting the inclusion and exclusion criteria. Data were analyzed using Fisher’s exact test. Out of 1,861 pregnant women, 361 (19.4%) developed preeclampsia. A total of 344 patients met the inclusion criteria, of whom 292 (84.9%) had complicated preeclampsia. Based on parity, 95 (32.5%) were nulliparous and 197 (67.5%) were multiparous. Fisher’s exact test showed no significant association between nulliparity and the occurrence of complicated preeclampsia (p = 1.000; OR = 1.007; 95% CI: 0.537–1.889). There was no significant association between nulliparity and the occurrence of complicated preeclampsia at Arifin Achmad Regional General Hospital during the 2019–2022 period.